MOLECULAR SIMULATIONS OF METAL ADSORPTION TO BACTERIAL SURFACES - Johnson K.J.; Cygan R.T.; Fein J.B. (My University, 2006)
The atomic-scale interactions that occur between cations and the metal-binding cell wall components common to many gram-positive bacteria were investigated using molecular simulations techniques. We examined the adsorption of Cd and Pb onto peptidoglycan and teichoic acid components of the bacterial cell wall using classical energy force field methods. Within the framework of molecular mechanics and the Cerius2 modeling software, we used energy minimization, conformational analysis, and molecular dynamics to examine the different components of the cell wall and to determine relative binding energies and structural configurations of the cell wall components, both with and without the metals present. Electronic structure calculations of representative metal-organic complexes validate the more practical classical methods required in simulating the large number of atoms associated with the cell wall components. The classical force field simulations were conducted in both gas phase and solvated periodic cells. Force field-based simulation techniques can adequately describe the interactions of Cd with the cell wall, defining both metal ion coordinations and binding distances. However, the classical force field approach is inconsistent in describing the observed Pb-cell wall interactions due to possible limitations in the force field parameters, the propensity for Pb to form hydroxides at circumneutral pH, or the dominance of other adsorption mechanisms.